Epidural Oxycodone for Acute Pain - Panu Piirainen; Hannu Kokki; Merja Kokki (MDPI AG, 2022)
Epidural analgesia is commonly used in labour analgesia and in postoperative pain after major surgery. It is highly effective in severe acute pain, has minimal effects on foetus and newborn, may reduce postoperative complications, and enhance patient satisfaction. In epidural analgesia, low concentrations of local anaesthetics are combined with opioids. Two opioids, morphine and sufentanil, have been approved for epidural use, but there is an interest in evaluating other opioids as well. Oxycodone is one of the most commonly used opioids in acute pain management. However, data on its use in epidural analgesia are sparse. In this narrative review, we describe the preclinical and clinical data on epidural oxycodone. Early data from the 1990s suggested that the epidural administration of oxycodone may not offer any meaningful benefits over intravenous administration, but more recent clinical data show that oxycodone has advantageous pharmacokinetics after epidural administration and that epidural administration is more efficacious than intravenous administration. Further studies are needed on the safety and efficacy of continuous epidural oxycodone administration and its use in epidural admixture.